Những câu hỏi liên quan
Trần Thị Đào
Xem chi tiết
Bùi Bảo Châu
20 tháng 1 2017 lúc 14:06

a)\(\frac{-5}{13}+\left(\frac{3}{5}+\frac{3}{13}-\frac{4}{10}\right)=\frac{-5}{13}-\frac{3}{5}-\frac{3}{13}+\frac{4}{10}=\left(\frac{-5}{13}-\frac{3}{13}\right)+\frac{4}{10}-\frac{3}{5}=\frac{-5-3}{13}+\left(\frac{4}{10}-\frac{6}{10}\right)=\frac{-8}{13}+\frac{-2}{10}=\frac{-80}{130}+\frac{-26}{130}=\frac{-106}{130}=\frac{-53}{65}\)

Bình luận (4)
ICHIGO HOSHIMIYA
Xem chi tiết
Hoàng Văn Dũng
Xem chi tiết
2015
Xem chi tiết
violympic
Xem chi tiết
Nguyễn Phi Hòa
7 tháng 6 2015 lúc 8:36

                                                    Giải:         

Đặt \(A=13\frac{1}{4}-2\frac{5}{27}-10\frac{5}{6},B=1\frac{3}{7}+\frac{10}{3},C=12\frac{1}{3}-14\frac{2}{7}\)

Ta có:             

\(A=13-2-10+\frac{1}{4}-\frac{5}{27}-\frac{5}{6}=1+\frac{27-20-90}{108}=1-\frac{83}{108}=\frac{25}{108}\)              

\(A.230\frac{1}{5}=\frac{25}{108}.230\frac{1}{25}=\frac{25}{108}.\frac{5751}{25}=\frac{5751}{108}=\frac{213}{4}\)                        

\(A.230\frac{1}{25}+46\frac{3}{4}=\frac{213}{4}+\frac{187}{4}=100\)                     

\(B=1+\frac{3}{7}+3+\frac{1}{3}=4+\frac{3}{7}+\frac{1}{3}=4+\frac{16}{21}=\frac{100}{21}\)                               

\(C=12\frac{1}{3}-14\frac{2}{7}=12-14+\frac{1}{3}-\frac{2}{7}=-2+\frac{7-6}{21}=-\frac{41}{21}\)            

\(B:C=\frac{100}{21}:\left(-\frac{41}{21}\right)=-\frac{100}{41}\)                

\(E=\frac{A.230\frac{1}{25}+46\frac{3}{4}}{B:C}=\frac{100}{-\frac{100}{41}}=-41\)

Bình luận (0)
Khánh Xuân
Xem chi tiết
Trần Tiến Pro ✓
10 tháng 7 2019 lúc 20:33

\(\text{a) }\left(-\frac{1}{16}\right)^{100}=\frac{\left(-1\right)^{100}}{16^{100}}=\frac{1}{16^{100}}\)

\(\left(-\frac{1}{2}\right)^{500}=\frac{\left(-1\right)^{500}}{2^{500}}=\frac{1}{\left(2^5\right)^{100}}=\frac{1}{32^{100}}\)

Ta co 

\(16^{100}< 32^{100}\)

\(\Rightarrow\frac{1}{16^{100}}>\frac{1}{32^{100}}\)

\(\Rightarrow\left(-\frac{1}{16}\right)^{100}>\left(-\frac{1}{2}\right)^{500}\)

Bình luận (0)
응 우옌 민 후엔
6 tháng 9 2019 lúc 15:55

a. 

Ta có:

\(\left(-\frac{1}{16}\right)^{100}=\frac{\left(-1\right)^{100}}{16^{100}}=\frac{1}{16^{100}}\)

\(\left(-\frac{1}{2}\right)^{500}=\frac{\left(-1\right)^{500}}{2^{500}}=\frac{1}{\left(2^5\right)^{100}}=\frac{1}{32^{100}}\)

Vì \(\frac{1}{16^{100}}>\frac{1}{32^{100}}\Rightarrow\left(-\frac{1}{16}\right)^{100}>\left(-\frac{1}{2}\right)^{500}\)

b.

Ta có:

\(\left(-32\right)^9=\left[-\left(2^5\right)\right]^9=-\left(2^{45}\right)\)

\(\left(-16\right)^{13}=\left[-\left(2^4\right)\right]^{13}=-\left(2^{52}\right)\)

Vì \(-\left(2^{45}\right)>-\left(2^{52}\right)\Rightarrow\left(-32\right)^9>\left(-16\right)^{13}\)

#Chúc bạn học tốt!#

Bình luận (0)
Tagami Kera
Xem chi tiết
Nguyễn Đình Trung
Xem chi tiết
☘️✰๖ۣۜYuηi✰☘️
Xem chi tiết
☘️✰๖ۣۜYuηi✰☘️
27 tháng 3 2020 lúc 9:26

Mong các bạn giúp mk nha ❤❤❤

Bình luận (0)
 Khách vãng lai đã xóa